Plan de negocios para la creación de una empresa de Mystery Shopper especializada en el sector cooperativo - Carbali Castro, Melissa Estefanía (2016)
This paper proposes a business plan for a company specializing in the Mystery Shopper Cooperative sector. The aim of this study was to determine the commercial and financial feasibility of undertaking this business. The business idea arises from the need that was identified in the market, for a specializing company of Mystery Shopper in financial services, to measure the Index Customer Satisfaction, and also propose improvement plans identifying the problem in service management. For which, the measurement model was implemented Servqual service. The target market for which strategies were developed in the promotional mix are the Cooperative Savings and Credit active in Quito. Being a new company the strategies was based on the lifting of qualitative and quantitative information focused in the customer, to enable market penetration and generate attracting potential customers.